After victory institutions, strategic restraint, and the rebuilding of order after major wars - Ikenberry, G. John (Princeton University Press, 2001)
The end of the Cold War was a ""big bang"" reminiscent of earlier moments after major wars, such as the end of the Napoleonic Wars in 1815 and the end of the World Wars in 1919 and 1945. Here John Ikenberry asks the question, what do states that win wars do with their newfound power and how do they use it to build order? In examining the postwar settlements in modern history, he argues that powerful countries do seek to build stable and cooperative relations, but the type of order that emerges hinges on their ability to make commitments and restrain power